Active Site Identification and Evaluation Criteria of In Situ Grown CoTe and NiTe Nanoarrays for Hydrogen Evolution and Oxygen Evolution Reactions. Issue 5 (20th March 2019) - Yang, Liu; Xu, Haoxiang; Liu, Huibing; Cheng, Daojian; Cao, Dapeng
Abstract: Developing efficient non‐precious bifunctional electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is highly critical for overall water splitting. Herein, vertically aligned CoTe and NiTe nanoarrays are synthesized in situ grown on Ni foams (marked as CoTeNR/NF and NiTeNR/NF) via a facile hydrothermal method, and further explore their catalytic activities for overall water splitting. The CoTeNR/NF catalyst exhibits not only excellent OER performance with a low overpotential of 350 mV to deliver 100 mA cm −2, but also high HER activity only requiring 202 mV overpotential to yield 10 mA cm −2 in alkaline condition. Moreover, experimental technique and density functional theory are combined together to reveal that the real active sites of CoTeNR/NF for OER are from the in situ generated CoOOHspecies on CoTeNR/NF in the OER process, and also propose a new HER performance evaluation criteria of using H2 O adsorption energy, H2 O dissociation barrier, and H2 /OH − desorption energy as an indicator. The new criteria can satisfactorily evaluate the HER performance of as‐synthesized samples, while the traditional one of using H adsorption energy as an indicator fails in the HER performance evaluation of as‐synthesized samples. It is expected that the new evaluation criteria can be used as a general criteria to evaluate the HER performance of other electrocatalysts. Abstract : The in situ grown CoTe and NiTe nanoarrays are synthesized as high‐performance bifunctional catalysts for overall water splitting. The active species of as‐synthesized catalysts for OER are identified by experiments and theoretical calculations, and a new theoretical evaluation criteria for HER is proposed, which can be used as a general criteria to evaluate the HER performance of other electrocatalysts.